Key Research Challenges in Digital Twin Applications for Demanufacturing. Issue 10 (2022) - Abumadi, Farah A.; Semeraro, Concetta; Olabi, Abdul Ghani; Dassisti, Michele
Abstract: Based on relevant studies, demanufacturing processes on end-of-life products may achieve around 70% material-saving, 60% energy-saving, and 50% cost-saving of the overall life-cycle cost. Despite these great benefits, many issues are still open in real-life applications, such as the unavailability of smart technology implementations that make more effective and efficient demanufacturing processes. The Digital twin application seems to be a promising tool to facilitate recycling, tracking, and managing such processes. This paper reviews the state-of-the-art research on digital twins for manufacturing and demanufacturing. A comprehensive analysis of the key challenges in applying digital twins for the demanufacturing process and potential solutions for the current challenges are provided.